2019
DOI: 10.1002/er.4465
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic model of a plate fin heat exchanger with catalytic coating as a steam reformer of methane, biogas, and dimethyl ether

Abstract: Summary The paper presents an analysis of a compact plate fin heat exchanger with catalytic coating. The unit is used to convert various fuels into hydrogen‐rich gas, which is then fed into the anodic compartments of a solid oxide fuel cell (SOFC) stack. The study looks at the fuel processor for methane, biogas, and dimethyl ether (DME). In the first phase, the reaction kinetics model was based on data from the literature. This was followed by tuning and validation of the numerical model using data collected d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The authors of the article have previously conducted work related to modeling the reforming process. A mathematical model of a compact plate fin heat exchanger with catalytic coating was presented in [1]. Four values of the steam-to-carbon ratio (2.0, 2.5, 3.0 and 3.5) were used to analyze the performance of the heat exchanger, which was investigated in a temperature range of 500 to 750 • C. It was found that the relative prediction error of the simulator did not exceed 3.5%.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of the article have previously conducted work related to modeling the reforming process. A mathematical model of a compact plate fin heat exchanger with catalytic coating was presented in [1]. Four values of the steam-to-carbon ratio (2.0, 2.5, 3.0 and 3.5) were used to analyze the performance of the heat exchanger, which was investigated in a temperature range of 500 to 750 • C. It was found that the relative prediction error of the simulator did not exceed 3.5%.…”
Section: Introductionmentioning
confidence: 99%